Biomarker microRNA-371a-3p - expression in malignancies other than germ-cell tumours - Gazanfer Belge; Markus Klemke; Bendix Hansen; Cansu Dumlupinar; Aylin Igde; Dirk Arnold; Hans Salwender; Christian Wülfing; Armin Soave; Klaus-Peter Dieckmann (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose microRNA-371a-3p (M371) is considered a highly sensitive and specific serum biomarker of testicular germ cell tumours (GCTs). However, little is known about the expression of M371 in nontesticular malignancies (NTMs), so far. As knowledge about the expression of the marker in other malignancies is a prerequisite for the clinical application of the test we aimed to explore the M371 expression in other cancers. Methods M371 serum levels were measured in 137 patients with NTM of 12 different neoplastic entities using the IVDR-certified M371-Test for quantitative real-time PCR. Median M371 serum levels and percentages of M371 level elevations were calculated for the entire NTM group and for entity-specific subgroups. The results were compared with GCT patients (n = 20) and with tumour-free male controls (n = 20) using descriptive statistical methods. Results Eight patients with NTMs had M371 serum level elevations, corresponding to a false-positive rate (FPR) of 5.84% (95% confidence intervals (CIs) 2.55–11.18%). Expression rates in GCTs and controls were 100% and zero, respectively. Thus, the specificity of the M371-Test for GCT is 94.90% (95% CI 90.21–97.77%) when all NTMs and tumour-free controls are considered. Remarkably, three out of 5 patients with multiple myeloma had elevated M371 levels. Conclusion The false-positive rate of the M371-Test in other malignancies than GCT is very low, and almost identical with that in healthy males, corresponding to a high specificity of 94.9% for detection of GCT. The surprising finding of M371 elevations in patients with multiple myeloma needs further investigation.